اختصاص المحكمة الجنائية الدولية بالنظر في جرائم اإلبادة الجماعية المرتكبة في فلسطين المحتلة - عبابسة إكرام; عبيد سارة (جامعة الوادي University of El Oued, 2025)
تُسلّط هذه المذكرة الضوء على أن العدالة الجنائية الدولية لا تزال تواجه تحدياتٍ جسيمة في التطبيق العملي، لا سيما عند التعامل مع قضايا ذات أبعاد سياسية مُعقّدة كالقضية الفلسطينية. ورغم وجود أطر قانونية تُنظّم المساءلة عن الجرائم الجسيمة، إلا أن تفعيلها يعيفه عوائق قانونية واختلال في الإرادة الدولية. ويُبيّن هذا الواقع أن تحقيق العدالة لا يتوقف فقط على وجود القانون، بل أيضًا على توافر الإرادة الدولية لاحترامه وتطبيقه بنزاهة وموضوعية. This memo highlights that international criminal justice still faces significant challenges in practical application, particularly when dealing with cases of complex political dimensions such as the Palestinian issue. Despite the existence of legal frameworks governing accountability for serious crimes, their activation is hampered by legal obstacles and imbalanced international will. This reality demonstrates that achieving justice is not solely dependent on the existence of law, but also on the availability of international will to respect and implement it fairly and objectively.
Keywords: اختصاص المحكمة الجنائية الدولية بالنظر في جرائم الإبادة الجماعية المرتكبة في فلسطين المحتلة; The International Criminal Court has jurisdiction to consider crimes of genocide committed in occupied Palestine.